Law Enforcement Against Lesbian, Gay, Bisexual, and Transgender (LGBT) Phenomena in The Qanun Jinayah in Aceh - Khairani, Khairani (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study revealed the implementation of Islamic Law in Aceh, especially those relating to Lesbian, Gay, Bisexual, and Transgender (LGBT) Phenomena. The aim is to find out how the law is enforced and what things hinder its application. Although Aceh has enacted Islamic Shari'a, and Aceh's Jinayah Qanun has banned LGBT actions through which the perpetrators are subject to sanctions the whip, but the phenomenon of LGBT in this Province still exists. The study found the fact that the Jinayat Qanun in this region had not been fully able to ensnare LGBT perpetrators, especially Lesbians (musahaqah) and homosexual (liwath). This is because of two main obstacles: first, the formal aspects involving the evidentiary aspect, and, secondly, the material aspects relating to legal rules that can be used to punish the perpetrators of these crimes.